Transformation of the Transport Framework of Eurasia in the Beginning of the 21st Century - A. G. Dankov; E. V. Savkovich (Международная аналитика)
For centuries, Eurasia has played a key role in shaping global trade and cultural ties. Transport corridors have been the arteries through which goods, ideas, and people have circulated, determining the economic and political development of regions. Throughout history, these corridors have undergone significant transformations, reflecting the evolution of technology, geopolitical realities, and economic priorities. From the legendary Silk Road to modern transcontinental routes, the history of Eurasian transport corridors is a history of continuous development and adaptation to changing conditions. This paper presents the results of a study aimed at analyzing the transformation of Eurasia’s transport framework that began after the collapse of the USSR and continues to this day. The analysis was conducted taking into account the impact of transport corridors on economic development, optimization of existing routes, and assessment of the development potential of new ones. The analysis of the transformation of the Eurasian transport framework was based on a systems approach – the study of transport corridors as complex systems that include various types of transport (rail, road, air and others), infrastructure, logistics centers, customs procedures, and the legislative framework. Particular attention is paid to identifying the relationships between the elements of the system and their impact on the functioning of the corridors. The transformation of the continent’s transport system, from railways to container ships, has contributed to economic growth, cultural exchange and integration of countries, but has also given rise to new challenges that require solutions in the 21st century. The development of Eurasian transport corridors is an ongoing process that will continue to shape the appearance of the continent and influence the destinies of peoples.